2019
DOI: 10.3390/nano9121761
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the Properties of Reduced Graphene Oxide and Nitrogen-Doped Reduced Graphene Oxide Produced by Thermal Reduction toward Efficient ORR Electrocatalysts

Abstract: N-doped (NrGO) and non-doped (rGO) graphenic materials are prepared by oxidation and further thermal treatment under ammonia and inert atmospheres, respectively, of natural graphites of different particle sizes. An extensive characterization of graphene materials points out that the physical properties of synthesized materials, as well as the nitrogen species introduced, depend on the particle size of the starting graphite, the reduction atmospheres, and the temperature conditions used during the exfoliation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…These values are greater than those reported for traditional carbon aerogels prepared via the pyrolysis of sol–gel-derived resin precursors at 2500 °C (at ∼5 nm [ 44 ]), yet lower than those reported for aerogels produced by subjecting a graphene oxide-based 3D graphene to high-temperature annealing (at crystallite sizes of >40 nm, and as high as 150 nm [ 34 ]). It shows that the crystallite size decreases with respect to the activation temperature which is due to the presence of defects due to doping levels of nitrogen and this is consistent with the earlier reported work [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
“…These values are greater than those reported for traditional carbon aerogels prepared via the pyrolysis of sol–gel-derived resin precursors at 2500 °C (at ∼5 nm [ 44 ]), yet lower than those reported for aerogels produced by subjecting a graphene oxide-based 3D graphene to high-temperature annealing (at crystallite sizes of >40 nm, and as high as 150 nm [ 34 ]). It shows that the crystallite size decreases with respect to the activation temperature which is due to the presence of defects due to doping levels of nitrogen and this is consistent with the earlier reported work [ 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
“…After nitrogen-doping, n value increased to 3 (Table 3), indicating that N-graphene promotes oxygen partial and complete reduction pathways simultaneously, with possible formation of HOOand OHspecies. This combined 2 and 4 electrons reduction process has also been reported in other works for nitrogen-doped carbon-based electrocatalysts 28,[37][38][39] .…”
Section: Resultssupporting
confidence: 84%
“…For example, Chai et al (2019) reported a b value of 75.4 mV dec -1 for a solid carbon spheres electrocatalyst 49 . Ramirez-Barria et al (2019) prepared a nitrogen-doped reduced graphene oxide electrocatalyst through the thermal annealing of reduced graphene oxide in ammonia-containing atmosphere at 700 °C, which was synthesized from a modified Brodie's method using 100 mesh graphite powder 39 . This electrocatalyst's b value was 99 mV dec -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nitrogen-doped carbon materials have attracted great attention due to their potential as critical metal-free catalysts, [18][19][20] their semi-conducting properties or their capacity to provide good anchors for metal nanoparticle nucleation. 21,22 Synthesized by arc-discharge-based synthesis, 23 chemical vapor deposition (CVD), 24 thermal treatment, 25,26 metallothermic reduction 27 or plasma treatment, 28 high quality N-doped carbon materials can also be prepared through direct solvothermal-based synthesis. [29][30][31][32] However, only a few examples of solvothermal synthesis of N-doped graphenic materials have been reported so far.…”
Section: A Introductionmentioning
confidence: 99%